2019
DOI: 10.3390/app9010141
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Efficiency Analysis of a Photovoltaic System with Different Module Technologies under Temperate Climate Conditions

Abstract: This study presents a comparative analysis of energy production over the year 2015 by the grid connected experimental photovoltaic (PV) system composed by different technology modules, which operates under temperate climate meteorological conditions of Eastern Poland. Two thin film technologies have been taken into account: cadmium telluride (CdTe) and copper indium gallium diselenide (CIGS). Rated power of each system is approximately equal to 3.5 kWp. In addition, the performance of a polycrystalline silicon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 40 publications
2
22
0
1
Order By: Relevance
“…Wider band gap materials (1.7-1.9 eV for a-Si [20,21], 1.45-1.5 eV for CdTe [22], 1.04-1.68 for CIGS [23]) are more resistant to the temperature growth; thus, their temperature coefficient is lower than for narrow bandgap polycrystalline silicon (pc-Si) (1.1 eV). The influence of the temperature on the performance of PV modules is visible well in the investigations conducted before, under the temperate climate of Poland [24], where significant differences between summer and winter conditions are observed. The role of temperature and other climate elements is an important issue but the quality of devices comprising the whole PV system also significantly influence the final performance of the installation.…”
Section: Introductionsupporting
confidence: 68%
“…Wider band gap materials (1.7-1.9 eV for a-Si [20,21], 1.45-1.5 eV for CdTe [22], 1.04-1.68 for CIGS [23]) are more resistant to the temperature growth; thus, their temperature coefficient is lower than for narrow bandgap polycrystalline silicon (pc-Si) (1.1 eV). The influence of the temperature on the performance of PV modules is visible well in the investigations conducted before, under the temperate climate of Poland [24], where significant differences between summer and winter conditions are observed. The role of temperature and other climate elements is an important issue but the quality of devices comprising the whole PV system also significantly influence the final performance of the installation.…”
Section: Introductionsupporting
confidence: 68%
“…Nevertheless, in recent years the share of photovoltaic installations in the national RES balance in Poland has been increasing. Further development of this part of the renewable energy sector is associated, inter alia, with a reduction in the costs of installations and with new technical solutions [55,56].…”
Section: The Use and Substitution Of Energy Carriers In Poland With Amentioning
confidence: 99%
“…Gulkowski et al [12] carried out a comparative analysis of energy production by a grid-connected experimental PV system composed of various technology modules, which operates in the temperate-climate meteorological conditions of eastern Poland, for the year 2015. The study revealed that the copper indium gallium diselenide (CIGS) technology demonstrated the highest energy production and performance ratio, as well as the lowest observed temperature-related losses.…”
Section: Performance Assessmentmentioning
confidence: 99%